Perancangan Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) di CV XYZ - Frederick Laurent Hartono (Jurnal Titra, 2021)
CV XYZ is a manufacturing industry company that is specialized in karoseri construction and it produces public vehicle bodies. This company has vehicle bodies as its main product such as ELF Microbus, Medium Bus and Big Bus. Back in 2020, it was reported that CV XYZ faced a problem, in which it had 11 work accidents. To overcome the existing problem, it is necessary to have a Safety Management System Design and an Occupational Health. The design of SMK3 itself is started by making direct observations in the barracks during working hours, conducting interviews with the Director and the Head of Production, and asking for work accident data to support it. The design of SMK3 will be implemented according to the company's ability and its valid regulations (Government Regulation number 50 of 2012). SMK3's final result is going to be a document or a guide book containing the policies, commitments, and procedures that have been designed by the author to support the SMK3 in CV XYZ.